Physical activity, sleeping pattern, and road accidents among Saudi population in Najran Province during the month of Ramadan - Mohamed, Hatem; Nasser, Ramzi Naim; Abbas, Anass M.; Shalabi, Manar G.; Eltayeb, Lienda Basheir; Hamid Babikr, Walid Gaafar (Intelektual Pustaka Media Utama, 2025)
This study examined the impact of Ramadan fasting on physical activity and sleep patterns among Saudis in Najran, Saudi Arabia. Seventy-three male and female volunteers completed a self-reported questionnaire over five days at Najran University Hospital. Data collected included demographics, physical activity levels, sedentary behaviors, sleep duration, social activities, and mood changes. Results showed that only 29 participants (39.9%) considered themselves physically active, while 44 (60.3%) were sedentary. The mean age of the active group was 41.60±8.21 years. Among females, only 7 (31.8%) were physically active, while 15 (68.2%) were inactive. Factors such as night work, mood changes, and indoor social activities significantly influenced physical activity levels (p<0.005). Regarding sleep, the physically active group had a mean daily sleep duration of 7.43±1.52 hours, while the sedentary group slept an average of 10.20±2.11 hours, showing a statistically significant difference. These findings suggest that Ramadan fasting influences both physical activity and sleep patterns, potentially affecting overall health and well-being.